Research Utilization and Evidence-Based Practice in Education and Nursing Practice - Yulis Setiya Dewi; Smriti Kana Mani (Jurnal Ners, 2020)
Editorial: Research Utilization and Evidence-Based Practice in Education and Nursing Practice